Incorporating Trust into Combinatorial Auctions: What Does Trust Cost? - Airy, Guruprasad; Chen, Po-Chun; Mullen, Tracy; Yen, John (Proceedings of the 2009 IEEE/WIC/ACM International Joint Conference on Web Intelligence and Intelligent Agent Technology - Volume 03, 2009)
As the use of automated negotiations becomes more mainstream, one key attribute that needs to be incorporated is a measure of a seller's trust or reliability. In this paper, we describe a combinatorial auction mechanism that allows buyers to specify their preferences over both an item and the seller's trustworthiness, and use it to generate a bid for a bundle of items. We consider some implications of generating a combined trust rating for a bundle of resources that are supplied by more than one seller. We show that allowing buyers to specify trust preferences leads to a higher overall utility and task completion rate than when compared with a model that does not consider seller trustworthiness.